PACIFISM AND THE MILITARY - A PERSPECTIVE - Bloom, J.B. (Scientia Militaria - South African Journal of Military Studies, 2012)
Anti-war feeling is perhaps as old as warfare itself. There are, for example, ancient Chinese and Persian poems that are powerful expressions of pacifism. The pacifist phenomenon is thus nothing new, and it is indeed understandable that as a reaction against the undoubted horrors of war there should be some in every age who would be inclined to reject it entirely. Others would seek only that when war is waged it is justifiable and as limited in its ill-effects as possible. For still others, however, war and conquest is an end in itself, the glory and heroism of victory and battle holding out the promise of an inspiring vision. These three positions are, of course, overdrawn. Nevertheless, it is the tensions between these three types of perspective, including here the complexities of intermediate and overlapping positions, that determine the background and provide the dynamic for confrontation between pacifism and the military.